Computer Based Learning in the Malay Language for Children with Dyslexia - OTHMAN, NURUL AINA (Universiti Teknologi Petronas, 2011)
The aim of this project is to develop a multimedia learning aid (SpleXia) to facilitate Malay word recognition, recall and usage by dyslexic children, based on studies of cognitive information processing. The objective is to demonstrate a 15% improvement in word recognition and replication, over a two-week period with SpleXia, among dyslexic children. Dyslexia is a condition where an individual having difficulties reading because the brain does not able to recognize and process certain symbols. The idea of this project arose from a needs assessment of the reading problems faced by dyslexic children, which affects their performance in daily life and academic enviromnents. Current therapeutic approaches to the treatment of dyslexia in Malaysia are often ineffective as they usually involve drill-based activity that-creates stress for children, parents and therapists during clinical sessions as well as the special education teachers in remedial classes. Such approaches also often foster an over-dependence on teachers, excluding independent self-learning by children and participatory involvement by parents. The reason why SpleXia targets to aid dyslexic children to improve their reading skill in Malay is because Malay is the national language of Malaysia thus it is being used widely in this country. Besides, the needs assessment also revealed a shortage of computer-based learning aids for dyslexic children in the Malay language. Benchmarking of existing Malay educational software was carried out. The application developed in this study is differentiated by (1) the placement of word cues in enviromnental settings, and (2) a stronger linkage between cues and relevant interests within the target age group. The target user of SpleXia is dyslexic children aged between 7-11 years old. According to Piaget' s cognitive development theory, children that belong to this age group are at the concrete operational stage where they see things in logical and